Near infrared photopolymer for micro‐optics applications. Issue 13 (10th June 2020) - Dika, Ihab; Diot, Frédéric; Bardinal, Véronique; Malval, Jean‐Pierre; Ecoffet, Carole; Bruyant, Aurélien; Barat, David; Reig, Benjamin; Doucet, Jean‐Baptiste; Camps, Thierry; Soppera, Olivier
Abstract: Near infrared (NIR) activable photopolymers suitable for versatile fabrication of micro‐optical elements were developed. The first main objective of this article is to show that these new photopolymers can be used for microfabrication and investigate the parameters governing the microfabrication process. The impact of photonic, physico‐chemical, and chemical parameters is discussed. High quality microstructures with a good control over their size and shape are demonstrated. The second main objective is to show practical examples of microlenses and waveguides implemented on single core and multiple core optical fibers, VCSELs, and glass slides are then presented. The NIR photosensitivity of this negative tone photoresists allows using the device source itself as to start the crosslinking process, which constitutes a convenient approach for micro‐optics self‐positioning on NIR sources and justifies the interest of such NIR photopolymer for the fabrication micro‐optical elements and optical interconnects. Abstract : A near‐infrared (NIR) photopolymer for the fabrication of micro‐optical elements by direct writing in the NIR region was developed and investigated. The photosensitivity of this negative‐tone photoresist allows using the NIR‐light source itself to start the crosslinking process, which constitutes a new approach for micro‐optics integration on NIR sources. Practical examples of microlenses and waveguides implemented on single‐core and multiple‐core optical fibers, vertical‐cavity surface‐emitting lasers (VCSELs), and glass slides are presented.